Level crossing rate of Nakagami-m fading signal: Field trials and validation - Yacoub, M. D.; Barbin, M. V.; de Castro, M. S.; Vargas, J. E. (Institute of Electrical and Electronics Engineers (IEEE), 2000)
Field trial measurements are used to validate the level crossing rate formula derived in an exact manner recently for the Nakagami-m signal. The formula reveals an excellent fit to measurements in situations other than those for which the Rice model is more appropriate.